On the use of lithogenic tracer measurements in aerosols to constrain dust deposition fluxes to the ocean southeast of Australia - C. Hird; M. M. G. Perron; M. M. G. Perron; T. M. Holmes; S. Meyerink; C. Nielsen; A. T. Townsend; P. de Caritat; M. Strzelec; A. R. Bowie; A. R. Bowie (Aerosol Research)
Australia contributes a significant amount of dust-borne nutrients (including iron) to the Southern Ocean, which can stimulate marine primary productivity. A quantitative assessment of the variability in dust fluxes from Australia to the surrounding ocean is therefore important for investigating the impact of atmospheric deposition on the Southern Ocean's carbon cycle. In this study, lithogenic trace metals (aluminium, iron, thorium, and titanium) contained in aerosols collected between 2016 and 2021 from kunanyi / Mount Wellington in lutruwita / Tasmania (Australia) were used to estimate dust deposition fluxes. Lithogenic fluxes were calculated using each tracer individually, as well as an average using all four tracers. This latter approach enabled an assessment of the uncertainty associated with flux calculations using only individual tracers. Elemental ratios confirmed the lithogenic nature of each tracer in aerosols when compared with both Australian soil samples and the average Earth's upper continental crust. Lithogenic flux estimates showed annual dust deposition maxima during the austral summer, following the Australian dust storm season, and annual minimum deposition flux over winter. The data provided here will help to constrain model estimates of Southern Hemisphere atmospheric deposition fluxes and their subsequent impact on global ocean biogeochemical cycles.